Quadriceps Strength and Knee Function After Anterior Cruciate Ligament Reconstruction with Quadriceps Tendon Bone Autograft: A Preliminary Report - Hofer, Kevin; Lucas, Brennen; Prohaska, Daniel; Zackula, Rosalee; Manske, Robert (Kansas Journal of Medicine, 2022)
Introduction. The purpose of this study was to evaluate quadriceps strength and knee function after anterior cruciate ligament (ACL) reconstruction using a quadriceps tendon bone (QTB) autograft. Methods. Preliminary data were extracted from an ongoing prospective cohort study in which the operative extremity was compared to non-operative extremity. Patients from 14 to 40 years of age who had an ACL reconstruction with QTB autograft volunteered to have knee assessment including quadriceps isokinetic strength measures and functional knee testing at 6 and 12 months postoperatively. Paired t-tests were conducted to compare postoperative strength and function scores on participants who had minimum 1-year post-surgical follow-up. Results. Patients had a significant recovery of quadriceps strength as determined by isokinetic testing and single leg hop test. For 31 participants, quadriceps strength of the operative leg measured at 60 deg/sec was 63% of the non-operative leg at 6 months, increasing to 79% at 1 year (p < 0.001); when measured at 180 deg/sec, these values were 68% at 6 months, increasing to 82% at 1 year (p < 0.001). For 30 participants, single leg hop functional scores of the operative leg were 80% of the non-operative leg at 6 months, increasing to 91% at 1 year (p < 0.001). Conclusions. After QTB autograft for ACL reconstruction, there were significant gains in quadriceps strength and knee function from 6 months to 1 year postoperative. These findings indicate the QTB is an acceptable ACL reconstruction option.